Zarządzanie strategiczne w organizacjach niedochodowych - wyniki badań - Kwiecińska, Monika (Strategic Management in Non Profit Organizations - Results of Research, 2008)
Weaknesses in the process of management in non-profit organizations tend to the decrease the effectiveness of these organizations and are the barriers of their mission fulfillment. The results of empirical research made by the author in 120 non-profit organizations located in the territory of Lowe Silesia a lot of such weaknesses and a lot of problems in this area.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 171-176